attI1-Located Small Open Reading Frames ORF-17 and ORF-11 in a Class 1 Integron Affect Expression of a Gene Cassette Possessing a Canonical Shine-Dalgarno Sequence - Papagiannitsis, Costas C. (Antimicrob Agents Chemother, 2017)
By searching the Integrall integron and GenBank databases, a novel open reading frame (ORF) of 51 nucleotides (nts) (ORF-17) overlapping the previously described ORF-11 was identified within the attI1 site in virtually all class 1 integrons. Using a set of isogenic plasmid constructs carrying a single gene cassette (bla(GES-1)) and possessing a canonical translation initiation region, we found that ORF-17 contributes to GES-1 expression.